2019
DOI: 10.1038/s41427-019-0160-8
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature giant magnetostriction in single-crystal nickel nanowires

Abstract: Magnetostriction is the emergence of a mechanical deformation induced by an external magnetic field. The conversion of magnetic energy into mechanical energy via magnetostriction at the nanoscale is the basis of many electromechanical systems such as sensors, transducers, actuators, and energy harvesters. However, cryogenic temperatures and large magnetic fields are often required to drive the magnetostriction in such systems, rendering this approach energetically inefficient and impractical for room-temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Therefore, the heterojunction between the magnetic metallic film and the ferroelectric substrate induces the uniaxial magnetic anisotropy via the interface effect including the magnetoelastic effect, magnetostriction [ 5 , 24 , 25 ], DMI [ 21 , 22 ], and electron wave function interference at the interface through the Rashba effect [ 23 ]. This investigation revealed an electronic state modulated by the heterojunction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the heterojunction between the magnetic metallic film and the ferroelectric substrate induces the uniaxial magnetic anisotropy via the interface effect including the magnetoelastic effect, magnetostriction [ 5 , 24 , 25 ], DMI [ 21 , 22 ], and electron wave function interference at the interface through the Rashba effect [ 23 ]. This investigation revealed an electronic state modulated by the heterojunction.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the Ni/Cu(100), Fe/Cu(100), and Fe/MgO systems, the magnetic anisotropy is induced by the orbital-coupling and spin-flip at the interface [ 3 , 4 , 17 ]. Candidate phenomena that are useful for inducing magnetic anisotropy are the Dzyaloshinskii-Moriya interaction (DMI) [ 21 , 22 ], Rashba interaction [ 23 ], magnetoelastic effect, and magnetostriction [ 24 , 25 ]. These interactions and effects can also be induced by symmetry breaking and bonding at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Bragg coherent X-ray diffraction imaging (BCDI) allows the visualization of the local atomic lattice displacement of single nanoparticles or grains in three ISSN 1600-5775 dimensions. BCDI is compatible with operando measurements under different external stimuli, such as compression or tension, femtosecond laser light pulses, electric and magnetic fields allowing the visualization of evolving strain inside nanoparticles and ultimately the investigation of materials properties at the nanoscale (Clark et al, 2013(Clark et al, , 2014(Clark et al, , 2015Ulvestad et al, 2015Ulvestad et al, , 2017Pateras et al, 2019;Cherukara et al, 2017;Bjö rling et al, 2019;Takahashi et al, 2013;Newton et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Then, by collecting at least three reflections, the three-dimensional (3D) image of the strain tensor of a nanocrystal can be obtained. This unique capability will be crucial for investigating properties of crystalline materials where the knowledge of the crystallographic orientation with respect to the axis of external stimuli is imperative (Pateras et al, 2019;Newton et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that nickel nanomaterials can exhibit unprecedented compressive strength [ 21 ], have pesticidal properties [ 22 ], perform in fuel cells [ 23 ], or can be used as an effective catalyst [ 24 ]. Moreover, the versatility of nickel allows it to be synthesized in various forms, such as foam, wires, spheres, shells, or tubes [ 25 , 26 , 27 , 28 ]. There are numerous works in which PLAL technique was introduced to obtain nickel nanoparticles.…”
Section: Introductionmentioning
confidence: 99%